Symmetry of a partially-ligated state maintained by dynamics in a negatively cooperative system - Strawn, Rebecca; Murthy, Parvathi S.; Ettrich, Rüdiger H.; Pelczer, István; Carey, Jannette (Frontiers in Biophysics, 2024)
Symmetry was a key concept underlying the MWC model for allostery advanced in 1965 by Monod, Wyman, and Changeux. The reciprocal interactions of symmetrically-arranged identical subunits were proposed to stabilize multimeric assemblies together with the free energy from bound ligands that progressively favor a monomer-like state. Structural symmetry of subunits was assumed to be maintained in the partially-ligated states, even if ligand placement itself is not symmetric. Partially-ligated states can be populated sufficiently for experimental study only in negatively cooperative systems, which were not considered in the MWC model. The work reported here uses 1H, 13C, 15N, and 19F NMR to evaluate the structural symmetry of the hexameric arginine repressor of E. coli, a negatively cooperative system, with a single bound L-arginine ligand. The analysis indicates that the singly-ligated hexamer maintains structural symmetry as probed by these four NMR nuclei. The results are consistent with earlier molecular dynamics simulations suggesting that the global dynamics of the singly-ligated assembly are harnessed to maintain structural symmetry. The results extend MWC symmetry concepts to this negatively cooperative system, and indicate a role for global dynamics in allostery.